The handbook of strategic public relations & integrated communications - Caywood, Clarke L. (McGraw-Hill, 1997)
As the media grows more ruthless, the role of public relations has become increasingly complex and critical. Savvy businesspeople know that how a company conveys and maintains its image has never been more importantor more challenging. The Handbook of Strategic Public Relations & Integrated Communications is the definitive guide for communications professionals. Featuring the expertise of the world's foremost public relations and marketing authorities, it is the first book of its kind to combine the art and science of marketing, public relations and communications in one single resource. An indispensable reference guide to the best practices in every industry, this handbook features more than 40 information-packed chapters authored by the best minds in the business and covers cutting-edge tips, topics and techniques such as: